The length-weight relationship of the bigeye scad (Selar crumenophthalmus) captured by purseseiner from FMA 716 of North Sulawesi seawaters: A comparative study of the target species sizes on May and August 2022 - Sitanggang, Effendi P.; Budiman, Johnny; Sitanggang, Dyan F. D.; Lohoo, Anneke V.; Kalalo, Flora P. (Jurnal Ilmiah PLATAX, 2026)
Bigeye scad (Selar crumenophthalmus Bloch 1793) is rich source of proteins, Omega-3 fatty acids, and various important vitamins and minerals for human body, that makes the fish has an important economic value. Additionally, because of forming an important shoal on coastal seawaters, the fish is frequently captured, notably by purseseiners in an important quantity from the FMA 716 of North Sulawesi seawaters. The intensiveness captures of the fish may affect the sustainability and continuity life of the species. The research aims at analyzing some biological reproduction aspects of species based on gender and fishing season. The 400 samples, 200 tails on May and 200 tails on August 2022, have selected by a purposive random sampling from the captures. Data analisys refers to some common formulas, such as the length and weight size structure, sex and weight ratio, W-L relationship (W = aLb, W = weight, g), L = length (cmFL), a and b constants, condition factor (K), length at first capture (Lc50%). The legal size is determined by comparing the length at first capture (Lc50%) observed and at first maturity (Lm50%) reference. On May, the sample weight is 33,439 g (51.8% of 400 samples), the sex and weight ratios are 1:1.08 and 1:1.36 respectively with the conversion factor (cf) of 1.26. The average length and weight sizes are 21.62 ± 0.17 cm and 167.20 ± 5.15 g respectively, where the average weight per 1 cmFL is 7.67 ± 0.18 g. The L-W relationship follows W = 0.1492 L 3.0785 (r = 0.86) for male, W = 0.0566 L 3.8088 (r = 0.90) for female, and W = 0.0864 L 3.4940 (r = 0.91) for all, with K average of 1.60 ± 0.02 for male, 1.66 ± 0.03 for female, and 1.63 ± 0.02 for 200 samples. On August, the sample weight is 31,115 g (48.2% of 400 samples), the sex and weight ratios are 1:1.50 and 1:1.82 respectively, with cf of 1.21. The average length and weight sizes are 21.49 ± 0.16 cm and 155.58 ± 4.71 g respectively, where the average weight per 1 cmFL is 7.19 ± 0.17 g. The L-W relationship follows W = 0.1515 L 3.047 (r = 0.88) for male, W = 0.0789 L 3.5485 (r = 0.88) for female, and W = 0.0836 L 3.5023 (r = 0.90) for all samples, with K average of 1.50 ± 0.02 for male, 1.58 ± 0.03for female, and K of 1.55 ± 0.02 for 200 samples. On both fishing seasons, all captures are categorized a positive allometry (b>3) and 96.75% of captures has a legal size. All females have passed their first maturity stage. For this reason, the fishermen must consider carefully when they catch the fishes, outside of the two months. Considering the intensiveness of fishing activities to such species, it is indispensable since early for all stakeholders designing a regulation to limitate captutes by gender size and fishing seasons, for all species of high potential and economic value of high density of shoals. Key words: bigeye scad, biological reproduction aspects, FMA 716, North Sulawesi, fish conservationn